Market Positions of Carbonated Soft Drink Brands in Consumer’s Perception: An Exploratory Research - บัวพรมมี ณฐมน; พลโยราช ก่อพงษ์; ทัศนวัฒน์ สถิร (KKBS Journal of Business Administration and Accountancy, 2017)
The present research aims to examine how the market positions of carbonated soft drink brands including Pepsi, Coke, Seven Up, Sprite, Mirinda andFanta is perceived. This exploratory research employed a questionnaire to collect the data with 377 students at Khon Kaen University. The study results reveal that Seven Up and Sprite are perceived as non-cola and colorless while Pepsi and Coke are perceived as cola and having colors. Finally, Mirinda and Fanta are perceived as non-cola and colorful. The research result can be used as guidelines for marketers to plan their branding strategies to modify consumer’s brand perceptions to match those intended by the corporate and formulate their brand differentiation strategies for their uniqueness.